Construction of a Liquid Crystal-Based Sensing Platform for Sensitive and Selective Detection of l-Phenylalanine Based on Alkaline Phosphatase - Zhou, Lele (Langmuir : the ACS journal of surfaces and colloids, 2019)
The detection of l-phenylalanine (l-Phe) has become one of the most pressing issues concerning diagnosis and treatment of phenylketonuria in neonates; however, a simple and robust methodology is yet to be developed. Here, the application of novel liquid crystals (LCs)-sensing platform for sensitive, selective, and label-free detection of l-Phe was reported at the first time. We devised a strategy to fabricate the sodium monododecyl phosphate (SMP)-decorated LC sensing platform with the appearance of dark. Then, a dark to bright (D-B) optical images alteration of LCs was observed after transferring alkaline phosphatase (ALP) to the interface, owing to cleavage of SMP induced by ALP. LCs remained dark images after the SMP-decorated interface in contact with the pre-incubated ALP and l-Phe. Such optical appearance resulted from the inhibition of ALP by l-Phe, which was further verified by the isothermal titration calorimetry (ITC). The strategy was applied to sensing l-Phe, which have been proven to allow for sensitively and selectively differentiation of l-Phe from interfering compounds with similar aromatic groups, as well as seven other essential amino acids. More importantly, the detection limit of l-Phe reached 1 pg/mL in urine samples, further demonstrating its value in the practical applications. Results obtained in this study clearly demonstrated the superiority of LCs toward the l-Phe detection, which can pave a way for the development of high performance and robust probes for l-Phe detection in clinical applications